2014
DOI: 10.1523/jneurosci.0981-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

The Expression Pattern of a Cav3-Kv4 Complex Differentially Regulates Spike Output in Cerebellar Granule Cells

Abstract: The cerebellum receives sensory information by mossy fiber input from a multitude of sources that require differential signal processing. A compartmentalization of function begins with the segregation of mossy fibers across 10 distinct lobules over the rostrocaudal axis, with tactile receptor afferents prevalent in anterior lobules and vestibular input in caudal lobules. However, it is unclear how these unique signals might be differentially processed at the circuit level across the cerebellum. As granule cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 64 publications
1
36
1
Order By: Relevance
“…In cerebellar granule cells, for example, synaptic inputs from mossy fibers may induce hyperpolarizing shifts in both half‐activation and half‐inactivation voltages of K V 4 channels, thereby invoking long‐term increase in granule cell excitability (Rizwan, Zhan, Zamponi, & Turner, ). Furthermore, in cerebellar granule and stellate cells, T‐type Ca 2+ (Ca V 3) channels form a signaling complex with K V 4 and the Ca 2+ ‐sensing KChIP, whereby Ca V 3‐mediated Ca 2+ influx significantly enhances I SA by causing depolarizing shift of K V 4 half‐inactivation voltage (Anderson et al, ; Heath et al, ; Molineux, Fernandez, Mehaffey, & Turner, ). The physiological significance of this Ca V 3‐K V 4 signaling complex is further underlined by the findings that Ca V 3 current density critically determines regional differences in membrane excitability and spike output of granule cells (Heath et al, ), and that extracellular Ca 2+ may regulate inhibitory outputs from stellate cells to cerebellar Purkinje cells (Anderson et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cerebellar granule cells, for example, synaptic inputs from mossy fibers may induce hyperpolarizing shifts in both half‐activation and half‐inactivation voltages of K V 4 channels, thereby invoking long‐term increase in granule cell excitability (Rizwan, Zhan, Zamponi, & Turner, ). Furthermore, in cerebellar granule and stellate cells, T‐type Ca 2+ (Ca V 3) channels form a signaling complex with K V 4 and the Ca 2+ ‐sensing KChIP, whereby Ca V 3‐mediated Ca 2+ influx significantly enhances I SA by causing depolarizing shift of K V 4 half‐inactivation voltage (Anderson et al, ; Heath et al, ; Molineux, Fernandez, Mehaffey, & Turner, ). The physiological significance of this Ca V 3‐K V 4 signaling complex is further underlined by the findings that Ca V 3 current density critically determines regional differences in membrane excitability and spike output of granule cells (Heath et al, ), and that extracellular Ca 2+ may regulate inhibitory outputs from stellate cells to cerebellar Purkinje cells (Anderson et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in cerebellar granule and stellate cells, T‐type Ca 2+ (Ca V 3) channels form a signaling complex with K V 4 and the Ca 2+ ‐sensing KChIP, whereby Ca V 3‐mediated Ca 2+ influx significantly enhances I SA by causing depolarizing shift of K V 4 half‐inactivation voltage (Anderson et al, ; Heath et al, ; Molineux, Fernandez, Mehaffey, & Turner, ). The physiological significance of this Ca V 3‐K V 4 signaling complex is further underlined by the findings that Ca V 3 current density critically determines regional differences in membrane excitability and spike output of granule cells (Heath et al, ), and that extracellular Ca 2+ may regulate inhibitory outputs from stellate cells to cerebellar Purkinje cells (Anderson et al, ). Consequently, it is likely that dominant‐negative effects of SCA19/22‐associated mutants on voltage‐dependent gating of K V 4.3 WT may similarly result in aberrant network excitability in the cerebellar circuits, which may in part manifest some of the ataxic features observed in the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is highly likely that Cav3 channels represent the physiological source of Ca 2+ for an acute gating modulation of membrane-bound Kv4.2/KChIP3 channels. In fact, Heath and coworkers [91] found out that regional differences in Cav3 channel expression directly correlated with the voltage-dependent I SA availability, and blocking Ca 2+ currents abolished regional differences in I SA density. The novel form of subcellular Ca 2+ signaling occurs within a protein complex, and the radius of action actually represents a Ca 2+ nanodomain (distance < 50 nm) [14,90].…”
Section: Acute Modulation Of the Kv4/kchip Channel Complex By Cytoplamentioning
confidence: 99%
“…Cerebellar dysfunction results in ataxia and dystonia, and more recently has been implicated in autism spectrum disorder (Fatemi et al, 2012; Wang et al, 2014). A single canonical circuit is thought to underlie all cerebellar computations (Eccles et al, 1967; Schmahmann, 2004), although regional differences have been observed (Cerminara et al, 2015; Dino et al, 1999; Heath et al, 2014; Witter and De Zeeuw, 2015). …”
Section: Introductionmentioning
confidence: 99%